EU enlargement and institutional development: How far away are the EU's Balkan and Black Sea neighbors? - Felix Hammermann; Rainer Schweickert (Kiel Institute for World Economics (IfW), 2005)
Institutional development in new and potential member countries determines the success of both the catching-up of developing European countries and the deepening of the European integration process. This paper argues that the timing of future enlargement should depend on institutional convergence between the EU and potential accession candidates. Therefore, the paper looks at institutional quality in the EU, in the EU's neighboring Balkan and Black Sea regions, and especially in Bulgaria, Romania, Croatia, Turkey, and Ukraine, i.e. the next countries in the queue for entry or likely to lobby for entry into the EU. Three dimensions of institutional quality - legislative, administrative, and judicative institutions - are analyzed on the basis of the World Bank Governance Indicators using institutional quality in EU member states as a benchmark in order to reveal institutional deficits.
Keywords: O10; F15; P20; 330; Transitional Economies; EU Enlargement; Regional Integration; Economic Development; Institutions; EU-Erweiterung; Institutionelle Infrastruktur; Gesetzgebung; Öffentliche Verwaltung; Übergangswirtschaft; Bulgarien; Rumänien; Kroatien; Türkei; Ukraine